A Study of Isotherms and Kinetics of Mangifera Indica Bark Adsorbent Used for Fluoride Removal form Drinking Water - Kumar, A.; Maurya, N. S. (Engineering, Technology & Applied Science Research, 2022)
In this paper, we have investigated the bark of mango (Mangifera Indica) as an adsorbent for fluoride removal. Chemical treatment and aluminum hydroxide coating increased the adsorption capacity of the adsorbent from 0 to 15mg/g. Aluminum hydroxide-coated adsorbent (Al-MIBAC) was subjected to a batch study by considering different operational parameters such as adsorbent dose, reaction time, and pH. The kinetics of the adsorbent strongly followed second-order behavior, indicating the chemo-sorption adsorption process. The R2 value for Langmuir isotherm is 0.999 and it was found to be fitted well with the experimental data. It is hence assumed that the adsorption of fluoride is homogeneous and monolayer. The maximum fluoride adsorption amount of Al-MIBAC was 56.81mg/g, which was superior to those of other adsorbents derived from bark. Al-MIBAC was highly effective in reducing the fluoride concentration from 20mg/L to less or equal to 1.5mg/L which is safe for drinking purposes.